The financial stability of a company and its business model - Jabłoński, Adam (Management and Administration Journal, 2023)
The prevailing situation of global economic crisis drew attention to a number of important factors that from the point of view of enterprises operating in the market were not sufficiently presented. One such factor is undoubtedly the concept of financial stability and financial security of a company. The purpose of this article is to discuss some aspects of the design and operationalization of the business models of companies with respect to ensuring the company’s financial stability at every stage of its operation. The essence of the problem, which the author defines the is a design of a business model in the life cycle of this model, with the lowest expenditures in the management process to achieve financial stability. The author argues that the essence of achieving financial stability of a company is based on the designed structure of its business model.